Pembuatan Media Penelusuran Informasi tentang Kejahatan Berbasis Website di Kepolisian Resor Kota Padang - Pinky, Regina Ullya; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
This paper discusses the Making of Website Based Search Information Media at Padang City Police. With the existence of web-based media can be a means of liaison between Polresta with Polsek in city / regency. So that the provision of services and information from the police to the public will be faster. The method used is descriptive method. Data was collected through direct observation at Polresta Padang. After making observations, the next step is to design key points that will be included on the paper and the page will be displayed on the website design. After that, design a database table that will be linked to the website design. Based on the research results can be concluded steps of making media search information about crime based website in Polresta Padang as follows: (1) Creating database; (2) Make connections; (3) Create a web page consisting of web display design, create login form, Create User Input, Displays User data. Therefore, it is suggested to members of Police Precinct Padang to use web as media to search information Polresta Padang. The Web is an information search medium whose coverage is very wide and accessible 24 hours, and the information contained therein can be updated quickly and does not require a high cost.Keyword: information, website